Analisis Pengaruh Customer Relationship Management terhadap Loyalitas Dengan Kepuasan Pelanggan sebagai Variabel Intervening (Studi pada Pelanggan Smartphone Vivo di Sidoarjo) - Dewi Rochmah; Sugeng Purwanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Smartphones have become a basic human need, so many companies deploy various strategies to maintain customer satisfaction and loyalty, one of which is through Customer Relationship Management (CRM). This study aims to analyze the influence of customer relationship management on loyalty with customer satisfaction as an intervening variable. The research population is all Vivo smartphone customers in Sidoarjo. In this study using a sample of 54 respondents. The non-probability sampling method in purposive sampling is the technique used in sampling. While the data analysis technique uses Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The research results show that Customer Relationship Management (CRM) has a positive and significant effect on customer satisfaction and loyalty, customer satisfaction has a positive and significant impact on customer loyalty, and customer satisfaction is an intervening variable that is able to mediate the influence of Customer Relationship Management (CRM) on customer loyalty.